First Reported Death of a Postpartum Woman Due to Coronavirus Disease 2019 in Nepal: A Lesson Learnt - Shrestha, A.P.; Bhushal, N.; Shrestha, A.; Tamrakar, D.; Adhikari, P.; Shrestha, P.; Shrestha, A.; Karmacharya, B.; Basnet, S.; Tamrakar, S.R.; Shrestha, R.; Shrestha, R. (Kathmandu University Medical Journal, 2020)
The first case of coronavirus disease 2019 was reported on December 31, 2019 in Wuhan, China where the average case fatality rate was 6.1 ± 2.9%. There are 453 deaths as of September 24, 2020 in Nepal. We report the first death of a 29-years-old postpartum woman due to COVID-19 in Nepal who was referred from a rural health center to Dhulikhel Hospital. On arrival, she was taken to the acute respiratory zone of the emergency department to provide immediate lifesaving procedures. Despite the repeated resuscitative measures, return of spontaneous circulation could not be achieved. The real time polymerase chain reaction test was positive. Our case report highlights the importance of early clinical suspicion, importance of “safety first” in healthcare settings, and the chain of management in such patients. We consider the fact that a postpartum woman registered as the first case of COVID-19 related death in Nepal to be an area of further study.